1996
DOI: 10.1128/jb.178.13.3755-3762.1996
|View full text |Cite
|
Sign up to set email alerts
|

Loss of overproduction of polypeptide release factor 3 influences expression of the tryptophanase operon of Escherichia coli

Abstract: Expression of the tryptophanase (tna) operon of Escherichia coli is regulated by catabolite repression and by tryptophan-induced inhibition of Rho-mediated transcription termination. Previous studies indicated that tryptophan induction might involve leader peptide inhibition of ribosome release at the stop codon of tnaC, the coding region for the operon-specified leader peptide. In this study we examined tna operon expression in strains in which the structural gene for protein release factor 3, prfC, is either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…It was shown that a mutation that alters RF1 increased basal-level expression of the tna operon in strains with UAG or UAA as the tnaC stop codon, but not in strains with UGA as the stop codon (22). Additionally, inactivation of the structural gene for RF3 increased basal-level expression of the tna operon at least threefold (21,49), consistent with the role of RF3 in enhancing translation termination at UGA, UAG, and UAA stop codons (14,27). These results support the hypothesis that, in the presence of tryptophan, the nascent TnaC peptide inhibits ribosome release at the tnaC stop codon, thereby preventing Rho-dependent termination.…”
supporting
confidence: 76%
“…It was shown that a mutation that alters RF1 increased basal-level expression of the tna operon in strains with UAG or UAA as the tnaC stop codon, but not in strains with UGA as the stop codon (22). Additionally, inactivation of the structural gene for RF3 increased basal-level expression of the tna operon at least threefold (21,49), consistent with the role of RF3 in enhancing translation termination at UGA, UAG, and UAA stop codons (14,27). These results support the hypothesis that, in the presence of tryptophan, the nascent TnaC peptide inhibits ribosome release at the tnaC stop codon, thereby preventing Rho-dependent termination.…”
supporting
confidence: 76%
“…These stringent correlations between the suppressible codon and the species of altered RFs are thought to represent the selectivity of the stop codon by bacterial RF1 and RF2. Unlike RF1 and RF2, mutations in the RF3 gene (prfC) cause a suppression of all three stop codons Matsumura et al 1996;Yanofsky et al 1996;Crawford et al 1999). RF3 is thought to accelerate the dissociation of RF1 and RF2 from the ribosome in a GTP-dependent manner Pavlov et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that in the absence of RRF, a ribosome translating the tnaC Arg12 sequence is not liberated normally from the tnaC stop codon. It was also shown previously that the overproduction of RF3 influences the expression of tnaA of E. coli; however, the explanation for this observation was not known at that time (31). Previous studies also showed that RRF and RF3 were involved in peptidyl-tRNA dropoff from a translating ribosome (12,28).…”
Section: Discussionmentioning
confidence: 90%
“…RRF and EF-G as well as other factors, e.g., RF3 and IF3, then participate in the ribosome release/recycling process to provide ribosomal subunits for additional protein synthesis (13). Interestingly, the inactivation of prfC, the structural gene for RF3, has been reported to increase basal-level expression of the tna operon two-to threefold (31). Overexpression of prfC had the opposite effect: it reduced both the basal and induced levels of tna operon expression (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation